2012
DOI: 10.1097/ncc.0b013e31821f5eb5
|View full text |Cite
|
Sign up to set email alerts
|

Previous Chemotherapy Influences the Symptom Experience and Quality of Life of Women With Breast Cancer Prior to Radiation Therapy

Abstract: Findings suggest that clinicians need to use a multidimensional symptom assessment tool in women with breast cancer at the initiation of RT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
34
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 50 publications
6
34
1
Order By: Relevance
“…The between group differences in fatigue severity scores represent not only statistically significant, but clinically meaningful differences (Cohen’s d =1.5) (Osoba, 1999). Consistent with previous reports, patients in the high fatigue group had a poorer functional status (Dhruva et al, 2013; Hofso, Miaskowski, Bjordal, Cooper, & Rustoen, 2012) and a more severe comorbidity profile (Berger, Gerber, & Mayer, 2012). …”
Section: Discussionsupporting
confidence: 90%
“…The between group differences in fatigue severity scores represent not only statistically significant, but clinically meaningful differences (Cohen’s d =1.5) (Osoba, 1999). Consistent with previous reports, patients in the high fatigue group had a poorer functional status (Dhruva et al, 2013; Hofso, Miaskowski, Bjordal, Cooper, & Rustoen, 2012) and a more severe comorbidity profile (Berger, Gerber, & Mayer, 2012). …”
Section: Discussionsupporting
confidence: 90%
“…Consistent with previous reports, patients in both the higher morning and evening fatigue classes reported a poorer functional status [12,39] and a more severe comorbidity profile [40]. Compared to the Moderate Evening Fatigue class, decrements in functional status reported by patients in the High and Very High Evening Fatigue classes represent not only statistically significant but clinically meaningful differences in KPS scores (d=0.39, d=0.52, respectively) [41,42].…”
Section: Discussionsupporting
confidence: 87%
“…In the older age group, the patients’ KPS (i.e., 4.8%) and SCQ (i.e., 6.7%) scores uniquely explained relatively similar amounts of variance. While previous studies found positive associations between both poorer functional status (Dhruva, et al, 2013; Hofso, Miaskowski, Bjordal, Cooper, & Rustoen, 2012) and higher levels of comorbidity (Berger, Gerber, & Mayer, 2012) and more severe fatigue, findings from our study suggest differential age effects for these two characteristics. In the older patients, research is warranted to determine which comorbidities and/or associated treatments contribute to higher levels of both morning and evening fatigue.…”
Section: Discussioncontrasting
confidence: 98%